2020
DOI: 10.1007/s00038-020-01438-8
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and retirement: original analysis of responses to the English Adult Active Lives Survey

Abstract: Objectives: Opportunities for older adults to do physical activity may depend on other commitments. We wanted to see if reported physical activity was higher or lower among older adults depending on work status: full time, part-time work or retired.Methods: This is a secondary analysis of The Active Lives Survey 2016/17 in England. The dataset was used to see how active people were depending on employment or retirement status. Types of physical activity (PA) considered were: leisure, gardening, active travel a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 26 publications
3
12
0
2
Order By: Relevance
“…Results showed that retired individuals had lower odds of being insufficiently active than government employees. Our results corroborate the earlier findings that retired people have relatively more leisure time which they might utilize in walking or gardening type activities (Brainard, Cooke, Lane, & Salter, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Results showed that retired individuals had lower odds of being insufficiently active than government employees. Our results corroborate the earlier findings that retired people have relatively more leisure time which they might utilize in walking or gardening type activities (Brainard, Cooke, Lane, & Salter, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…We excluded adults reporting the equivalent of; 2520 min/week of moderate-intensity activity. This figure is the equivalent of >6 hours of moderate-intensity activity each of the week is lower than the 8-h/day cut-off used in older adults in a recent analysis of data from the Active Lives Survey [ 54 ] and maybe somewhat conservative as it is achievable if respondents partake in 3-h vigorous activity day Excluding this 6% of the sample inevitably reduce r estimate of how many adults met current physical activity recommendations. When these cases were considered in our sensitivity analysis ( S3 Table ) dg aerobic activity guidelines increased to 70.7%.…”
Section: Discussionmentioning
confidence: 87%
“…Contrary to previous qualitative research [ 31 , 40 ], our results showed neither capability nor motivation to be important correlates of sports participation in older adults. This perhaps indicates that adaptable changes in sports modality may need to go beyond capability or motivation, and stem into the changing lifestyles (e.g., retirement), roles within society and interests of older adults (i.e., opportunity) [ 33 , 34 ]. This may be understood by adopting participatory methodologies implemented in places, spaces, and environments.…”
Section: Discussionmentioning
confidence: 99%